Endocrine disorders among long-term survivors of childhood head and neck rhabdomyosarcoma. (February 2016) - Clement, S.C.; Schoot, R.A.; Slater, O.; Chisholm, J.C.; Abela, C.; Balm, A.J.M.; van den Brekel, M.W.; Breunis, W.B.; Chang, Y.C.; Davila Fajardo, R.; Dunaway, D.; Gajdosova, E.; et al.
Abstract: Purpose: Head and neck rhabdomyosarcoma (HNRMS) survivors are at increased risk of developing pituitary dysfunction as an adverse event of radiotherapy. Our aim was to investigate the frequency and risk factors for pituitary dysfunction in these survivors. Secondly, we aimed to compare the prevalence of pituitary dysfunction between survivors treated with external beam radiation therapy (EBRT) and survivors treated with the ablative surgery, moulage technique after loading brachytherapy, and surgical reconstruction (AMORE) procedure. Methods: Eighty HNRMS survivors treated in London (EBRT based) and Amsterdam (AMORE based: AMORE if feasible, otherwise EBRT) in the period 1990–2010 and alive ≥2 years post-treatment were evaluated. Survivors were evaluated in multidisciplinary late-effects clinics, with measurement of linear growth, determination of thyroid function, and growth hormone parameters. Additional data, such as baseline characteristics, anthropometrics, pubertal stage, and the results of additional laboratory investigations, were retrieved from patient charts. Results: Pituitary dysfunction was diagnosed in 24 in 80 (30%) survivors, after a median follow-up time of 11 years. Median time to develop pituitary dysfunction after HNRMS diagnosis was 3.0 years. Risk factors were EBRT-based therapy (odds ratio [OR] 2.06; 95% confidence interval [CI] 1.79–2.46), parameningeal tumour site (OR 1.83; 95% CI 1.60–2.17) and embryonal RMS histology (OR 1.49; 95% CI 1.19–1.90). Conclusions: Radiotherapy used for the treatment of HNRMS confers a significant risk of the development of pituitary dysfunction. AMORE-based treatment in children with HNRMS resulted in less pituitary dysfunction than treatment with conventional EBRT. Our findings underscore the importance of routine early endocrine follow-up in this specific population. Highlights: We investigated pituitary dysfunction in head and neck rhabdomyosarcoma (HNRMS) survivors. Pituitary dysfunction was diagnosed in 30% of HNRMS survivors. Ablative surgery, moulage technique after loading brachytherapy, and surgical reconstruction (brachytherapy) resulted in less pituitary dysfunction than conventional external beam radiation therapy. All childhood HNRMS survivors should be given routine endocrine follow-up.